Is Polycystic Ovary Syndrome Caused by Bulimia Nervosa? - Sh Jahanfar; J Aden (JRI, 2000)
Introduction: Ninety four females who attended at the ultrasound department of Royal Hospital for Women underwent a transabdominal ultrasound to detect polycystic ovaries (PCO). Material and methods: Thirty-seven individuals had scan normal ovaries and 38 had scan evidence of polycystic ovary (PCO). All the subjects were sent a bulimia investigation test (Edinburgh) (BITE) questionnaire for abnormal eating behavior. Results: A total of 76 responses was received (81 %). Overall, most of women with PCO had abnormal BITE score and their mean BITE score showed a significant increase compared to those with normal ovaries. BITE score was significantly correlated with age.